Anticancer Effects of Fufang Yiliu Yin Formula on Colorectal Cancer Through Modulation of the PI3K/Akt Pathway and BCL-2 Family Proteins - Dong, Bingzi; Yang, Zhenjie; Ju, Qiang; Zhu, Shigao; Wang, Yixiu; Zou, Hao; Sun, Chuandong; Zhu, Chengzhan (Frontiers in Cell and Developmental Biology, 2020)
Colorectal cancer (CRC) is one of the most common malignant tumors in China. Fufang Yiliu Yin (FYY) is a traditional Chinese medicine formula used in clinical practice for cancer treatment, but its effectiveness and mechanism of action in human CRC are unclear. In this study, we investigated the antitumor effect of FYY on HCT116 and SW480 human CRC cell lines in vitro and evaluated the underlying molecular mechanism. A subcutaneous xenograft mouse model was used to confirm the antitumor effect in vivo. The components and targets of FYY were collected from the TCMSP database. CRC targets were collected via the GeneCard and OMIM databases. Protein-protein interactions were explored using the STRING platform. Cytoscape was used to construct drug-disease-target networks. KEGG and GO analyses were performed to investigate common FYY and CRC targets. FYY significantly inhibited cell proliferation and induced HCT116 and SW480 cell apoptosis. Cell proliferation was blocked at the G0/G1 phase, while cell apoptosis was promoted at the early stage. According to the network pharmacological analysis, quercetin and kaempferol were the most bioactive compounds of FYY. The key targets of FYY were Cyclin-D1, MAPK8, and EGFR. GO analysis showed that core targets included the apoptotic signaling pathway, response to steroid hormone, and cellular response to organic cyclic compound. KEGG pathway analysis showed that FYY may affect CRC through the PI3K/Akt pathway. In vitro, FYY significantly inhibited tumor growth. Pathway analysis confirmed that FYY induced cell apoptosis by modulating PI3K/Akt signaling and BCL-2 family proteins. Hence, our findings indicate that FYY may be a promising adjuvant therapy for CRC.